Investigating The Influence of Paragraph Shrinking Strategy Towards Students’ Reading Comprehension at Senior High School - Nuraeni, Mega Afria; Indrasari, Nunun; Zakiyah, Zakiyah (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aimed to investigate the effect of the paragraph-shrinking strategy on reading comprehension at senior high school. The quantitative method with a pre-experimental design was used, involving pre-tests and post-tests to measure students' progress. This study revealed that implementing the Paragraph Shrinking strategy significantly improved students' reading comprehension. Statistical analysis using paired sample t-test showed a p-value of 0.000 <0.05), indicating a statistically significant effect of the intervention. The results confirmed that the null hypothesis (H₀), assuming no significant effect of the intervention, was rejected, while the alternative hypothesis (Hₐ), indicating a significant effect, was accepted. The strategy encouraged students to identify main ideas and summarize paragraphs, which improved their comprehension and retention of reading materials. Based on these findings, it can be concluded that the paragraph-shrinking strategy is efficacious in improving reading comprehension, especially in the context of narrative texts within the Merdeka Curriculum framework.